(untitled) (Linguostylistic Studies, 2015)
The article deals with the modality in linguistic researches. The article touches upon the issue of a short history of the category of modality in contemporary linguistics and text linguistics; also it highlights the author’s modality meaning in the process of literary text creation. Much attention is given to the differentiation of modality in syntax and text linguistics aspects. The authors modality is analyzed as a communicative-pragmatic and subjective-estimative category. The semantic basis of modality category is objective modality and subjective-estimative modality. It is spoken in detail about explication of national-cultural, dramatic and other author’s modality in contemporary fiction. Key words: modality, the author’s modality, text modality, subjective-estimative modality, literary text. References